Effect of Bian-stone and warm-ironing therapy with Traditional Chinese Medicine in the treatment of joint pain induced by knee osteoarthritis (中药砭石热熨技术治疗膝骨关节炎患者关节疼痛效果观察) - ZHEN Hong (甄红); ZHANG Xuejian (张雪键); CUI Yangfang (崔杨芳) (中西医结合护理)
Objective To investigate the effect of Bian-stone and warm-ironing therapy with Traditional Chinese Medicine (TCM)in the treatment of joint pain induced by knee osteoarthritis (KOA). Methods Totally KOA patients with joint pain were treated with Bian-stone and TCM warm-ironing therapy. The pain degree was measured by Visual Analogue Scale (VAS). Results In the degree of pain measured with VAS, there was significantly decreased after nursing intervention (P＜0. 05). Conclusion Bian-stone and warm-ironing therapy with TCM is effective to relieve the joint pain induced by KOA. (目的 探讨中药砭石热熨技术治疗膝骨关节炎(KOA)患者关节疼痛的效果。方法 选取30例KOA患者为研究对象, 实施中药砭石热熨以缓解疼痛。采用视觉模拟评分法(VAS)评估患者关节疼痛情况。结果 干预后患者疼痛减轻, 与干预前比较差异有统计学意义(P＜0. 05)。结论 中药砭石热熨技术的应用有助于缓解KOA患者关节疼痛, 值得借鉴。)